Target volume delineation and margins in the management of lung cancers in the era of image guided radiation therapy. Issue 1 (24th February 2014) - Lin, Robert
<x xml:space="preserve">Abstract</x> The goal of radiation therapy is to deliver a lethal dose of radiation to diseased tissue while minimising dose to surrounding healthy structures. Prior to the actual treatment delivery, treatment planning is the most critical part of a patient's radiation treatment management. The most crucial step is the accurate localisation and delineation of the target volume. The implementation of image guided radiation therapy in radiation treatment has reduced the impact of organ motions and set up errors. Can the increased precision mitigate the issues associated with target volume delineation? <boxed-text content-type="graphic" id="jmrs43-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>